926 Evaluating VTE Prophylaxis in Nephrectomy in Two Merseyside Hospitals. (12th October 2021) - Farmer, T; Calmuc, A; Wong, K; Starmer, B; Venugopal, S
Abstract: Aim: The primary aim was to review current venous thromboembolism (VTE) prophylaxis prescribing against national and European guidelines at two hospitals in northwest England. A secondary aim was to standardise VTE prescribing practices. Method: 3 standards were identified (NICE, BAUS and EUA) for VTE prophylaxis in nephrectomy. All simple and radical nephrectomies and nephroureterectomies were included. Open and laparoscopic cases were included. Data was collected from Royal Liverpool University Hospital (RLUH) and Arrowe Park Hospital (APH). Cases from surgical diaries between January 2019 to January 2020 were identified and compared to the 3 standards. 49 cases were identified at RLUH and 83 at APH Results: At APH, 77/83 (92.7%) cases received inpatient LMWH. The remaining 6 were already on a DOAC. 98.7% received inpatient mechanical VTE prophylaxis. 85.5% of patients received extended VTE prophylaxis with no documented indication, and only 20% of open nephrectomies received 28 days LMWH. At RLUH 44/49 cases (89.7%) received inpatient LMWH. All 5 patients who did not had a documented reason why. 100% of inpatients at received inpatient mechanical VTE prophylaxis. 4 patients underwent open nephrectomy, however none of these received 28-day extended LMWH prophylaxis. Conclusions: Comparing guidelines with local data reveals that prescribing practice for both in- and outpatient LMWH is variable and often is based on personal preferences. The above results have been presented locally at each institution and practice standardised with re-audit ongoing.